Acclimation of elk mating system following restoration to the Missouri Ozarks, U.S.A. Issue 7 (17th February 2022) - Pero, Ellen M.; Chitwood, M. Colter; Hildreth, Aaron M.; Berkman, Leah K.; Keller, Barbara J.; Sumners, Jason A.; Hansen, Lonnie P.; Isabelle, Jason L.; Eggert, Lori S.; Titus, Chelsea L.; Millspaugh, Joshua J.
Abstract : Biologists increasingly use translocation to restore animals to areas where they have been extirpated. However, we know little about how translocation decisions influence translocation‐mediated social dynamics. Breeding in polygynous ungulate mating systems is typically dominated by prime age males, but founding males within translocated ungulate populations often are comprised of only young individuals. We investigated the influence of releasing exclusively young‐aged males on mating system and male reproductive success during an elk ( Cervus canadensis ) restoration program in Missouri. From 2011 to 2013, we translocated and released 106 elk from Kentucky to Missouri, U.S.A. We collected tissue samples for DNA from all translocated elk and subsequently captured adults and calves in Missouri during 2014–2018 for paternity analysis. Initial levels of polygyny were low but increased and acclimated over the initial years following translocation, commensurate with advancing sire age structure and increasing population density. Sire age was positively associated with individual male reproductive success initially, but the effect of age decreased as polygyny acclimated and sire age structure became older and more variable. Polygyny levels in the reintroduced population were restored to expected values within 4 years of the last translocation event, demonstrating the acclimation of mating structure despite a translocation tactic favoring young‐aged males. Importantly, initial dampened polygyny may facilitate retention of genetic variation by maximizing the genetic contribution of more founding individuals; however, benefits to genetic variation retention should be considered against potential demographic consequences to calves sired by young males.